Hubungan antara Penggunaan Kateter Tenchkoff , Status Gizi, Pembedahan, dan Komplikasi pada Anak Dengan CAPD di RSUP dr. Mohammad Hoesin, Palembang - Tinton Ardiyan; Eka I Fitriana; Shalita Dastamuar; Ziske Maritska (Medula, 2021)
Chronic kidney disease is a detrimental health problem in children with increasing morbidity and mortality rates. CAPD as an option for renal replacement therapy provides superior benefits over conventional hemodialysis in children with terminal kidney disease. However, the effectiveness of CAPD in long term needs to be anticipated because of the risk of infectious and non-infectious complications. Cross-sectional study was conducted in the Medical Record Department of RSMH. The samples were pediatric patients with CAPD in June (2016-2021) with complete medical records. The Sample study was analyzed by univariate and bivariate. The relationship between risk factors and complications was analyzed using the Chi-square test. The subjects were 14 people, male, >5 years old, normal nutritional status (42.9%), had abnormality anatomy kidney (57.1%), and surgery by laparoscopy (71.4%). The most infectious complication is peritonitis (50%) and the non-infectious complication is poor drainage ( 42.9 %). There was no meaningful relationship among risk factors to complications in patients children with CAPD in RSMH (p>0.05). By the descriptive analysis, every factor plays a role in the incident of complications. However, no there is a meaningful relationship among factor risk of complications infectious and non-infectious.